2014
DOI: 10.1186/2193-1801-3-204
|View full text |Cite
|
Sign up to set email alerts
|

DWT features performance analysis for automatic speech recognition of Urdu

Abstract: This paper presents the work on Automatic Speech Recognition of Urdu language, using a comparative analysis for Discrete Wavelets Transform (DWT) based features and Mel Frequency Cepstral Coefficients (MFCC). These features have been extracted for one hundred isolated words of Urdu, each word uttered by ten different speakers. The words have been selected from the most frequently used words of Urdu. A variety of age and dialect has been covered by using a balanced corpus approach. After extraction of features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Various ways to perform automatic segmentations are Fourier Transform, Short Term Energy, Minimum Phase Group Delay Method, Wavelet Method, Discrete Wavelet Transform (DWT) and Word Chopper Technique [16]. In this proposed system we used DWT method for segmentation since it uses frequency and time concurrently due to that computing the threshold value will be accurate [17]. The DWT is defined as (1) i,j,k are integer values.…”
Section: A Segmentationmentioning
confidence: 99%
“…Various ways to perform automatic segmentations are Fourier Transform, Short Term Energy, Minimum Phase Group Delay Method, Wavelet Method, Discrete Wavelet Transform (DWT) and Word Chopper Technique [16]. In this proposed system we used DWT method for segmentation since it uses frequency and time concurrently due to that computing the threshold value will be accurate [17]. The DWT is defined as (1) i,j,k are integer values.…”
Section: A Segmentationmentioning
confidence: 99%
“…We randomly divide our data into train, validation and test sets with a ratio of 2 : 1 : 1 and observe the results for MFCCs as well as for features learned 4 A useful tutorial on SVM is available from Burges [17] 5 The dataset can be requested via email. 6 Previous experimentations with this dataset for speech recognition applications have been reported by [20,21].…”
Section: Experiments Preparationmentioning
confidence: 99%
“…Besides, the speech data used in their experimentation is limited to one particular accent only. Ali et al [13] have reported results on the same dataset of Urdu, as used in the work reported in this paper, and have analyzed the use of Discrete Wavelet Transform (DWT) features and compared the performance with MFCCs. They conclude their discussion in favor of using MFCCs.…”
Section: Related Workmentioning
confidence: 99%